63
Chat with our AI personalities
2z+9.75-7z=-5.15
(2z - 7)(z + 4)
z = 18.5 6z - 24 = 2z + 50 Take the -24 to the other side of the equals and change its sign; take the 2z to the other side of the equals and change its sign: => 6z - 2z = 50 + 24 => 4z = 74 Divide both sides by 4: => z = 18.5
Add like terms to like: (2z - 20) + (3z + 5) = (2z + 3z) + (-20 + 5) = 5z - 15 2z is shorthand for z+z, 3z is shorthand for z+z+z, so: 2z + 3z = (z+z) + (z+z+z) = z+z+z+z+z = 5z Or, to put it another way, just add the coefficients: 2z + 3z = (2+3)z = 5z.
z = 3.6